2003
DOI: 10.1116/1.1584473
|View full text |Cite
|
Sign up to set email alerts
|

Field emission characteristics of nodular carbon nanotubes

Abstract: A configuration of carbon nanotubes (CNTs) whose surfaces were fully covered with nanoscale nodes was developed in our laboratory. We named this material nodular CNTs or NCNTs. A hydrogen plasma process was used to turn common CNTs into NCNTs. Combined with this process, a technique has been developed to make planar NCNTs field emitters. Field emission experiments showed that planar NCNTs emitters had superior field emission characteristics. Specifically, the emission site density was increased by the order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[ 190 ] The authors showed recyclable CFRP composite structures where a full recycling of CF takes place due to thermoset dissolution and recovered polymer powder can be hot‐pressed to repair composites. Chemical methods to introduce imine, [ 191 ] cyclic acetal, [ 192 ] and hexahydro‐s‐triazine [ 193 ] groups into epoxy monomers endow dynamic thermosetting matrices for recyclable composite formation.…”
Section: Sustainability In Aerospace Polymer Materials: How To Get Th...mentioning
confidence: 99%
“…[ 190 ] The authors showed recyclable CFRP composite structures where a full recycling of CF takes place due to thermoset dissolution and recovered polymer powder can be hot‐pressed to repair composites. Chemical methods to introduce imine, [ 191 ] cyclic acetal, [ 192 ] and hexahydro‐s‐triazine [ 193 ] groups into epoxy monomers endow dynamic thermosetting matrices for recyclable composite formation.…”
Section: Sustainability In Aerospace Polymer Materials: How To Get Th...mentioning
confidence: 99%
“…One is the printing of CNTs containing binder resin on glass substrates and the other is the direct growth of CNTs on glass substrates by chemical vapor deposition (CVD). [1][2][3][4][5] The problem encountered in the printing method is that it is difficult to disperse the CNTs uniformly and to control the density and protruding length of the CNTs. In addition to the printing method, thermal, plasma and hot filament CVDs can be employed to grow CNTs directly on glass substrates.…”
Section: Introductionmentioning
confidence: 99%